2010
DOI: 10.3899/jrheum.090726
|View full text |Cite
|
Sign up to set email alerts
|

Male-only Systemic Lupus

Abstract: Systemic lupus erythematosus (SLE) is more common among women than men with a ratio of about 10 to 1. We undertook this study to describe familial male SLE within a large cohort of familial SLE. SLE families (two or more patients) were obtained from the Lupus Multiplex Registry and Repository. Genomic DNA and blood samples were obtained using standard methods. Autoantibodies were determined by multiple methods. Medical records were abstracted for SLE clinical data. Fluorescent in situ hybridization (FISH) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…This led the authors to infer that men were overrepresented as parents of offspring with SLE 37. However, because that study was composed of families with at least two SLE cases rather than being population based, it may have been subject to selection biases, such as the inclusion of cases with greater genetic risk or disease severity, or a greater tendency for men with affected offspring to participate due to the rarity of SLE in men.…”
Section: Discussionmentioning
confidence: 99%
“…This led the authors to infer that men were overrepresented as parents of offspring with SLE 37. However, because that study was composed of families with at least two SLE cases rather than being population based, it may have been subject to selection biases, such as the inclusion of cases with greater genetic risk or disease severity, or a greater tendency for men with affected offspring to participate due to the rarity of SLE in men.…”
Section: Discussionmentioning
confidence: 99%
“…Not only do women and men differ in their normal immune response but there are also differences between them in the prevalence, presentation and severity of ADs. This leads to the notion that increased immune function imparts increased susceptibility to autoimmunity in women [2,18,84,85]. There are multiple hypotheses about the genetic mechanisms that could explain the sex bias in ADs.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Among families in which at least one SLE patient was a woman, only 19 of 48 (40%) female first-degree relatives had a positive ANA (p = 0.0006 compared to the relatives in the families with all male SLE) (15). Our patient’s persistent ANA negativity and anti-dsDNA positivity is atypical of what has previously been reported in this context.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, these same authors showed that the prevalence of renal disease (with or without a formal diagnosis of SLE using American College of Rheumatology diagnostic criteria) is significantly increased in female family members of men with SLE as compared to women with an affected female relative (68% versus 43%; P = 0.002). Subsequent studies suggest that for families with only affected male relatives, the etiology of SLE occurrence likely relates to a relatively greater genetic predisposition than is present in families with familial SLE but no (or relatively fewer) affected males (15). Although not studied directly, based on the current evidence and highlighted by our case, it can be inferred that the future risks of developing SLE and LN may be especially elevated for potential kidney donors who are first-degree relatives of SLE-affected men.…”
Section: Discussionmentioning
confidence: 99%